2010
DOI: 10.1177/070674371005501205
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends in Mortality Associated with Depression: Findings from the Stirling County Study

Abstract: Objective The question addressed is whether a mortality risk associated with depression in a 1952 representative sample of Stirling County adults changed in a new sample of 1970 and whether there was a change in relationships to cigarette smoking and alcoholism. Method Sample members were interviewed about depression and cigarette smoking. General physicians were interviewed by psychiatrists regarding alcoholism. Information about death as of December 31, 1992 was provided by Statistics Canada. Proportional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 52 publications
3
32
1
Order By: Relevance
“…The first linkage covered deaths that occurred through Dec. 31, 1992 (1047 deaths observed). 16 The second is a newly completed linkage of the Stirling County Study 1992 survivors (n = 2586) to the mortality database that covers deaths that occurred through Dec. 31, 2011 (1014 deaths observed). The database linkage was implemented using the Generalized Iterative Record Linkage System, 29,30 which generates probability ratios for each potential match between records in the study cohort and the Canadian Mortality Database based on participants' names, parents' names, date of birth, sex and postal code.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first linkage covered deaths that occurred through Dec. 31, 1992 (1047 deaths observed). 16 The second is a newly completed linkage of the Stirling County Study 1992 survivors (n = 2586) to the mortality database that covers deaths that occurred through Dec. 31, 2011 (1014 deaths observed). The database linkage was implemented using the Generalized Iterative Record Linkage System, 29,30 which generates probability ratios for each potential match between records in the study cohort and the Canadian Mortality Database based on participants' names, parents' names, date of birth, sex and postal code.…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports from the Stirling County Study showed increased risk of mortality among participants with depression in the 1952 sample who were followed through 1968 [17][18][19] and through 1992, 16 and increased mortality risk associated with depression among participants in the 1970 sample followed through 1992. 20 Here, we…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A steadily increasing body of literature continues to document an association between depression and mortality in elderly populations. 31,32 We cannot state that higher use of antidepressant medications was the cause of higher mortality across plans. It may be that the use of antidepressants is a marker for worse depression.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…For MDD, take away the stress and the depression persists. Furthermore, MDD is usually accompanied by other psychiatric disorders, especially anxiety and other medical disorders, 5 -6 with an increased risk of death from all causes, 7 especially cardiovascular diseases. In fact, MDD is associated with decreased heart rate variability and for those who are postmyocardial infarction, MDD is as potent a predictor of poor outcomes.…”
mentioning
confidence: 99%